Development of Data-Driven Digital Marketing for the ADIDES Website to Improve Awareness and Engagement - Wachda Yuniar Rochmah; M. Riyan Akbari; Fakhri Alauddin; Kurnia Afrida; Imelia Sugma Anugraturofi’i; Dwika Ayu Nurcahyaningsih; Sandra Aulia Divanti; Muhammad Farhansyah Mondari; Caesareano Lafado Yesa; Ananda Bintang Saputra (Abdi Masyarakat, 2026)
ADIDES (Asosiasi Dosen Integrator Desa) is a non-profit academic organization that promotes community empowerment through collaboration among lecturers, villages, and Village-Owned Enterprises (BUMDesa). However, limited digital content management and the absence of data-driven monitoring reduced the effectiveness of its website as a communication and outreach platform. This community service project aimed to strengthen the digital marketing performance of the ADIDES website through search engine optimization (SEO), content marketing, and web analytics implementation. The program employed a participatory approach consisting of problem identification, website assessment, keyword research, content development, implementation, and evaluation. As the primary outcome, 80 SEO-oriented articles were produced based on systematic keyword research to improve the website's organic visibility and traffic potential. In addition, a web analytics dashboard was developed to enable the ADIDES internal team to monitor website performance, including visitor trends, traffic sources, and content effectiveness for continuous evaluation. These outputs provide a sustainable, data-driven content management system that supports evidence-based decision-making and enhances organizational capacity in managing digital communication. The program demonstrates that integrating keyword-driven content strategies with performance monitoring can strengthen website awareness, increase stakeholder engagement, and support the long-term sustainability of digital community outreach.